The Morbidity of the Urodynamic Evaluation and the Correlation With Lower Urinary Tract Symptoms - Onur, Rahmi; Orhan, İrfan; Ardıçoğlu, Arslan; Atikeler, M. Kemal; Semerciöz, Atilla (Fırat University, 2001)
In the present study, the subjective and objective morbidity of urodynamic evaluation in patients with lower urinary tract symptoms(LUTS) was determined and the relationship to obstructive and irritative sypmtom scores was investigated with evaluating the overall tolerability of the procedure. Between April 1998 and November 1999, a total of 46 male patients with Benign prostatic hyperplasia (BPH) were included into the study. After urodynamics, the patients were evaluated by a questionnaire to assess the morbidity and by visual analog scale (VAS) to detect the overall discomfort and were divided into 3 groups. The mean residual urine volume, total, obstructive and irritative symptom scores of each group were compared. Thirty-eight (83%) patients found the procedure less bothering than they expected, whereas 8 (17%) patients found the procedure more bothering. There was no significant difference between groups I and II among age, total, obstructive and irritative symptom scores ( p>0.05 ). In group III, symptom scores and the residual urine were statistically higher than group I. The morbidity related to urodynamics is significantly lower in contrast to initial experiences. Thus, in the diagnosis and deciding the treatment modality of patients with LUTS, urodynamic evaluation is an effective diagnostic modality with minimal morbidity.

Bu çalışmada, alt üriner sistem semptomlu (AÜSS) hastalarda ürodinami sonrası gelişen subjektif ve objektif morbidite bulgularının belirlenmesi, obstrüktif ya da irritatif semptomlarla olan ilişkisi ve hastaların genel anlamda işlemi tolere etme oranları incelendi. Nisan 1998 ile Kasım 1999 tarihleri arasında incelenen ve benign prostat hiperplazisi (BPH) saptanan toplam 46 erkek hasta çalışmaya alındı. Ürodinami sonrası, hastalar morbidite ve genel rahatsızlık yönünden vizüel analog skala (VAS) ile değerlendirilerek 3 gruba ayrıldılar. Hastaların ortalama rezidüel idrar miktarları, total, obstrüktif ve irritatif semptom skorları ve yaşları ayrı ayrı karşılaştırıldı. İşlemin tolere edilmesi açısından hastalardan 38 (%83)'i işlemi beklediklerinden daha az ya da hiç, 8 (%17)'i ise daha fazla rahatsız edici olarak değerlendirdiler. Grup I ile orta düzeyde etkilenen II.gruptaki hastalar karşılaştırıldığında yaş, total, obstrüktif ve irritatif semptom skorları arasında anlamlı farklılık saptanmadı (p>0.05). Grup III'deki hastalarda ise semptom skorları ve rezidüel idrar miktarları grup I'deki hastalara oranla istatiksel olarak anlamlı farklılık gösterdi (p
ÜRODİNAMİ İNCELEMESİNE BAĞLI OLUŞAN MORBİDİTE VE ALT ÜRİNER SİSTEM SEMPTOMLARI İLE OLAN İLİŞKİSİ